The hidden twist: chronic uterine inversion masquerading in plain sight - M., Poojashree; N., Sunanda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Spontaneous non puerperal uterine inversion is an exceedingly rare gynaecological event. When it occurs, it is often due to an intrauterine polypoid mass attached to the uterine fundus, eventually pulling the uterus inside out over time as the mass increases in time. Here we present the cases of postmenopausal women presented with mass per vagina. A clinical diagnosis of chronic uterine inversion due to pedunculated submucous fibroid was made and was surgically managed.